Effect of intervention on screen time in preschoolers: a systematic review and meta-analysis of randomized controlled trials - Yan Wu; Xiaobin Xi; Chunkai Zhang; Jieying Jiang; Sunyue Ye (BMC Public Health)
Abstract Background Excessive screen time (ST) is linked to adverse physical and mental development in children, with habits forming in preschool and solidifying over time. Previous studies on interventions to reduce ST in preschoolers aged 0–7 years have shown inconsistent results. We conducted a systematic review and meta-analysis of randomized controlled trials (RCTs) to evaluate intervention effectiveness and identify potential moderators.  Methods We searched CNKI (Chinese), Wanfang Data (Chinese), SinoMed, Ebscohost, Web of Science, EMBASE, PubMed, and Cochrane Library for RCTs (January 1, 2000–December 31, 2024) targeting ST reduction in preschool children. Study quality was assessed using the Cochrane Risk of Bias Assessment tool and Jadad scale. Effect size were reported as standardized mean difference (SMD) with 95% confidence intervals (CI). Subgroup analyses (e.g., sample size, child age, gender, intervention duration) were conducted, with statistical tests (e.g., the chi-square test) comparing subgroup differences. Results A total of 41 studies with 14,514 participants were included in the meta-analysis. The overall summary of random effects showed a small, beneficial impact of ST interventions compared to controls (SMD = 0.26, 95% CI: 0.12 to 0.39). Subgroup analysis showed that the intervention effect was moderated by child age (χ2 = 6.25, P = 0.04), intervention duration (χ2 = 7.38, P = 0.007), target behavior of the intervention (χ2 = 6.72, P = 0.01) and intervention recipient (χ2 = 10.5, P = 0.01). Conclusion Despite heterogeneity in study methods and results, overall interventions to reduce ST in early childhood show significant reductions, suggesting that this may be an opportune time to intervene. Future research should explore strategies for implementing large-scale interventions and sustaining long-term intervention effects, investigate the potential impact of different theoretical frameworks on intervention outcomes, and examine the role of caregivers in supporting behavior change. These findings provide a robust foundation for developing evidence-based strategies to promote healthy ST habits in young children.